2018
DOI: 10.1080/10409289.2018.1496722
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation and Academic Measures Across the Early Elementary School Grades: Examining Longitudinal and Bidirectional Associations

Abstract: This study evaluated the association between children's (N = 301) self-regulation and math and reading achievement in kindergarten, first grade, and second grade. Children's self-regulation was assessed using the Head-Toes-Knees-Shoulders (HTKS) task (involving control of gross body movements) and a computerized continuous performance task (CPT; assessing primarily inhibitory control) in kindergarten, first grade, and second grade. Research findings: Based on cross-lagged structural equation panel models, HTKS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 58 publications
6
37
0
1
Order By: Relevance
“…This pattern suggests that self-regulation and math skills codevelop and reinforce one another across the transition from kindergarten to the early primary grades, which is consistent with work from other samples over the same period of development (Kim, Duran, Cameron, & Grissmer, 2017). Furthermore, Hernández et al (2018) found that children who began school with relatively weak academic skills but had better self-regulation measured with the continuous performance task had higher reading and math achievement. Hernández et al's (2018) findings have implications for children who enter school academically at risk or behind their peers, because these appear to be the students who would benefit most from interventions and activities that target inhibitory control-based self-regulation.…”
Section: Themes From This Special Sectionsupporting
confidence: 83%
See 3 more Smart Citations
“…This pattern suggests that self-regulation and math skills codevelop and reinforce one another across the transition from kindergarten to the early primary grades, which is consistent with work from other samples over the same period of development (Kim, Duran, Cameron, & Grissmer, 2017). Furthermore, Hernández et al (2018) found that children who began school with relatively weak academic skills but had better self-regulation measured with the continuous performance task had higher reading and math achievement. Hernández et al's (2018) findings have implications for children who enter school academically at risk or behind their peers, because these appear to be the students who would benefit most from interventions and activities that target inhibitory control-based self-regulation.…”
Section: Themes From This Special Sectionsupporting
confidence: 83%
“…Furthermore, Hernández et al (2018) found that children who began school with relatively weak academic skills but had better self-regulation measured with the continuous performance task had higher reading and math achievement. Hernández et al's (2018) findings have implications for children who enter school academically at risk or behind their peers, because these appear to be the students who would benefit most from interventions and activities that target inhibitory control-based self-regulation. Although school is an obvious place where children get practice in self-regulation, out-of-school time also matters and deserves more prominence as a context for development (Deutsch, Blyth, Kelley, Tolan, & Lerner, 2017).…”
Section: Themes From This Special Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, regulation refers to effortful control, the complementary traits of attentional focusing and inhibitory control. These findings were not surprising, as the impact of a child’s regulatory abilities on school achievement has been well-documented (e.g., [ 4 , 9 , 96 ]).…”
Section: Discussionmentioning
confidence: 81%